Penerapan Metode Diskusi Terbimbing untuk Meningkatkan Kemampuan Guru dalam Pembuatan RPP di SMKN 3 Gowa - Bolong, H. Karnedy (Jurnal Paedagogy, 2021)
The purpose of this study was to improve the ability of teachers in making lesson plans through guided discussions at SMKN 3 Gowa. The research used is school action research which is carried out in 2. This research instrument uses tests and non-tests. The data analysis technique used was descriptive which was carried out through three stages, namely: data reduction, data exposure, and inference. The results of this study indicate that the data in the first cycle with an average value of 59.7 with completeness of 43.3% and the ability of teachers to use lesson plans by 50% where these results have not reached the target set, then the action is taken in Cycle II by doing improvement of learning and lesson plans, so that learning outcomes increase to 72.0%. So it can be concluded that the guided discussion method can improve the ability of teachers in making lesson plans at SMKN 3 Gowa.